EVOLUTION OF THE SEDIMENTATION CONDITIONS IN CRETACEOUS IN THE AREA OF THE NORTH-WESTERN SHELF OF THE BLACK SEA - ISHCHENKO, I.; YAKUSHYN, L. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
Evolution of the sedimentation conditions in cretaceous in the area of the North-western shelf of the black sea has been described.